Bosnia and Herzegovina : First Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance of a Performance Criterion -Staff Report; Press Release; and Statement by the Executive Director. (IMF Staff Country Reports; Country Report, 2012)
Bosnia and Herzegovina's (Bah) economy started to lose steam in early 2012 as growth slowed in Europe. Intensification of the euro area crisis further affected Bin's growth outlook. However, measures such as limiting the expenditure at the central government level and targeting overall general government spending by 1 percentage point of GDP in 2013 aim to improve the economy. Comprehensive reforms of rights-based benefits are also identified, which are imperative for both medium-term fiscal sustainability and improving the functioning of labor markets.